Moral enhancement, freedom, and what we (should) value in moral behaviour. Issue 6 (25th January 2013) - DeGrazia, David
Abstract : The enhancement of human traits has received academic attention for decades, but only recently has moral enhancement using biomedical means – moral bioenhancement (MB) – entered the discussion. After explaining why we ought to take the possibility of MB seriously, the paper considers the shape and content of moral improvement, addressing at some length a challenge presented by reasonable moral pluralism. The discussion then proceeds to this question: Assuming MB were safe, effective, and universally available, would it be morally desirable? In particular, would it pose an unacceptable threat to human freedom? After defending a negative answer to the latter question – which requires an investigation into the nature and value of human freedom – and arguing that there is nothing inherently wrong with MB, the paper closes with reflections on what we should value in moral behaviour.